STUDY OF DRUGS' ANTHELMINTIC EFFICACY IN ANIMAL TREMATODOSES (Intent Research Scientific Journal, 2023)
This article describes the literature sources and their analysis on the effectiveness of anthelmintic drugs used in practice by scientists of our republic,the CIS, and foreign countries for the treatment and prevention of trematodes among agricultural and wild animals.